2017
DOI: 10.1038/aps.2017.164
|View full text |Cite
|
Sign up to set email alerts
|

A miRNA-200c/cathepsin L feedback loop determines paclitaxel resistance in human lung cancer A549 cells in vitro through regulating epithelial–mesenchymal transition

Abstract: Cathepsin L (CTSL), a cysteine protease, is closely related to tumor occurrence, development, and metastasis, and possibly regulates cancer cell resistance to chemotherapy. miRNAs, especially the miR-200 family, have been implicated in drug-resistant tumors. In this study we explored the relationship of CTSL, miRNA-200c and drug resistance, and the potential regulatory mechanisms in human lung cancer A549 cells and A549/TAX cells in vitro. A549/TAX cells were paclitaxel-resistant A549 cells overexpressing CTSL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 50 publications
1
24
0
1
Order By: Relevance
“…The expression levels of EMT markers showed that EMT was induced in Huh7/PTX cells, suggesting that EMT was positively associated with PTX resistance. This is consistent with a previous study that also indicated the association between EMT and PTX resistance by regulating the expression levels of E-cadherin, cytokeratin 18, N-cadherin and vimentin (20). Moreover, it was found that miR-212-3p inhibited PTX resistance by regulating EMT.…”
Section: Discussionsupporting
confidence: 93%
“…The expression levels of EMT markers showed that EMT was induced in Huh7/PTX cells, suggesting that EMT was positively associated with PTX resistance. This is consistent with a previous study that also indicated the association between EMT and PTX resistance by regulating the expression levels of E-cadherin, cytokeratin 18, N-cadherin and vimentin (20). Moreover, it was found that miR-212-3p inhibited PTX resistance by regulating EMT.…”
Section: Discussionsupporting
confidence: 93%
“…However, miRNAs can reduce the paclitaxel resistance. It has come to limelight less lately that miR-200c can overcome paclitaxel resistance via modulation of the cathepsin L (CTSL)- mediated epithelial-mesenchymal transition in A549 cells via feedback loop system [ 131 ]. Also, paclitaxel resistance was reversed by the overexpression of miR-107 in A549/Taxol cells.…”
Section: Paclitaxelmentioning
confidence: 99%
“…Similarly, Cathepsin A transcription was targeted by expressed mir106b-5p causing suppression of Colorectal Carcinoma (CRC) cell migration and invasion [76]. Interestingly, mir200c overexpression reduced Cathepsin L expression in lung A549 cells, resulting in enhanced susceptibility to Paclitaxel-mediated cell death and EMT suppression [77]. While, such recent studies link Cathepsin transcriptional expression to an alternative mode of regulation through the miRNAs, more importantly, such studies also highlight the relative importance of miRNA as a potential therapeutic in overcoming Cathepsin-mediated chemoresistance and Cathepsin-mediated EMT regulation [77].…”
Section: Signalling Network and Cathepsin Expressionmentioning
confidence: 99%
“…Interestingly, mir200c overexpression reduced Cathepsin L expression in lung A549 cells, resulting in enhanced susceptibility to Paclitaxel-mediated cell death and EMT suppression [77]. While, such recent studies link Cathepsin transcriptional expression to an alternative mode of regulation through the miRNAs, more importantly, such studies also highlight the relative importance of miRNA as a potential therapeutic in overcoming Cathepsin-mediated chemoresistance and Cathepsin-mediated EMT regulation [77]. As seen previously, mir152 has been linked to regulating Wnt-mediated EMT inhibition [78] and mir106b-5p with the regulation of key signaling intermediates such as GSK3B, VEGFA and PTK2 in colon and cervical cancers [79] and in both of which, Cathepsins A and L are seen to play a vital regulatory role.…”
Section: Signalling Network and Cathepsin Expressionmentioning
confidence: 99%